2017
DOI: 10.1111/ics.12397
|View full text |Cite
|
Sign up to set email alerts
|

Lipid‐based submicron capsules as a strategy to include high concentrations of a hydrophobic lightening agent in a hydrogel

Abstract: Lipid-based capsules (LNC), an encapsulation system useful for the epidermal delivery of hydrophobic compounds, were adapted to the encapsulation of a commercial lightening agent. The encapsulation permits the dispersion in a stable manner of a very high concentration of a hydrophobic active molecule in a hydrogel while maintaining the physicochemical and sensory properties of the gel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The initial fast release rate attributed to free Cl on the cubosome particle surface, while drug incorporated into the particle core has been released in a prolonged mode (Zhang et al, 2008, Zhuang et al, 2010). In addition, GMO as a basic cubosomes component might lead to decreasing the drug partitioning rate from the oily medium to the aqueous one when compared to the pure drug which could diffuse easily to the dissolution media (Nguyen et al, 2017, Patil et al, 2015, Sadanshio et al, 2015). This result was in agreement with the entrapping efficiency result.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial fast release rate attributed to free Cl on the cubosome particle surface, while drug incorporated into the particle core has been released in a prolonged mode (Zhang et al, 2008, Zhuang et al, 2010). In addition, GMO as a basic cubosomes component might lead to decreasing the drug partitioning rate from the oily medium to the aqueous one when compared to the pure drug which could diffuse easily to the dissolution media (Nguyen et al, 2017, Patil et al, 2015, Sadanshio et al, 2015). This result was in agreement with the entrapping efficiency result.…”
Section: Resultsmentioning
confidence: 99%
“…A transdermal multilayered patch consists mainly of basic components; polymers and drugs formulated in drug reservoir layer in the patch system. The drug reservoir layer is the most important one as it is the carrier of drug molecules and the controller of the drug release pattern (Ali, 2017, Nguyen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It has already been demonstrated that nanoencapsulation of lipophilic molecules can increase their concentration in a gel while keeping its pH, rheological or sensory properties unchanged [12,13]. Moreover, nanosystems have also been used to disperse homogeneously an active molecule in films for transdermal or dermal delivery [6,10,[14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The complexity of this nanostructure endowed itself with a large surface area, enabling cubosomes to achieve higher loading capacity and desirable drug release performance than simply round nanoparticles [111]. In a 2020 study, the drug entrapment efficiency and drug loading capacity of cubosomes were 97.7% and 9.9%, which are relatively high compared to other previously reported nanocarriers [112]. The treatment of cubosome-incorporated AT101 has improved cytotoxicity of LN229 by 20% than treated by free AT101, manifesting the promise of cubosome in the treatment of GBM [113].…”
Section: Cubosomesmentioning
confidence: 96%